Peran Keterlibatan Kerja Sebagai Mediator Pada Hubungan Pengaturan Kerja Fleksibel Terhadap Task Performance Karyawan Gen Z Di Lingkungan Kerja Hybrid - Pytaloka, Aurora Dewi; Ninawati , Ninawati; Idulfilastri, Rita Markus (Jurnal Locus Penelitian dan Pengabdian, 2025)
The hybrid work arrangement is increasingly preferred by Generation Z employees as it provides a balance between personal life and work. However, task performance in this setting varies, particularly regarding employee engagement levels. This study aims to examine the influence of flexible work arrangements on task performance with work engagement as a mediating variable. Flexible work arrangements are defined as an arrangement allowing employees freedom in choosing their working time and location, while work engagement refers to a positive state characterized by vigor, dedication, and full absorption in work. Task performance is defined as an employee’s ability to complete core tasks that support organizational goals. Participants in this study were 153 Generation Z employees working in hybrid arrangements in several companies in Jabodetabek. Data were collected using the Flexible Work Arrangements Questionnaire (FWAQ) for flexible work arrangements, the Utrecht Work Engagement Scale (UWES) for employee engagement, and the Individual Work Performance Questionnaire (IWPQ) in the (Task Performance) section for task performance. The results indicate that flexible work arrangements positively influence task performance, with employee engagement significantly mediating this relationship. These findings are expected to contribute to the development of work policies that support productivity and employee well-being in hybrid work environments.